Peran Badan Kesatuan Bangsa dan Politik dalam Meningkatkan Kesadaran Politik di Kabupaten Sidoarjo - Christanto, Septian Arie; Prathama , Ananta (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the role of the National Unity and Politics Agency (Bakesbangpol) of Sidoarjo Regency in increasing public political awareness. The method used is a qualitative approach with interview and observation techniques. The results of the study indicate that Bakesbangpol has an important role in political counseling, leadership training, and facilitating dialogue between the government and the community. However, there are still challenges in reaching all levels of society. This study is expected to provide recommendations for programs to increase political awareness in the region. Keyword: National Unity and Politics Agency, Political Awareness, Community